Collision-Free Local Path Planning: An Approach Using Skeletonization - Torres, Marcelo A.; Ramalho, Geraldo L. B. (Anais da Escola Regional de Computação Bahia, Alagoas e Sergipe (ERBASE), 2024)
This study proposes an approach to find collision-free paths in dynamic environments, employing skeletonization. For this purpose, regions of interest are identified based on best driving criteria, prioritizing the smoothness of the route. We demonstrate that the free area skeleton generates trajectories equidistant from obstacles, avoiding collisions.